Ścieżki rowerowe jako element przestrzeni miejskiej - główne problemy lokalizacji i konstrukcji = Bicycle paths within the urban area - main problems of their location and construction - Greinert, Andrzej; Fórmanowicz, Sebastian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the documents of the European Union and its agencies has been recorded communication by bike as a rightfull part of modern communication systems. Thus arose the problem of cycling organization - functional and safe.
Keywords: ścieżki rowerowe; drogi miejskie; gospodarka komunalna; bike paths; urban roads; municipal economy